PENGARUH BUDAYA ORGANISASI, ORGANIZATIONAL CITISENSHIP BEHAVIOR DAN DISIPLIN KERJA TERHADAP KINERJA PERSONEL POLRES PAMEKASAN - jurnalmap map; Eko Budi Waluyo; Indra Prasetyo; Chamariyah ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
ABSTRACT The purpose of this research is 1) To know and describe about organizational culture, Organizational Citizenship Behavior, work discipline and performance of personnel, 2) To find out whether organizational culture, Organizational Citizenship Behavior and work discipline simultaneously affect the performance of personnel, 3) To find out whether the organizational culture, Organizational Citizenship Behavior and work discipline partial effect on the performance of personnel, 4) To find out which variables among organizational culture, Organizational Citizenship Behavior and work discipline have a dominant influence on the performance of personnel. The results show that Based on the results of previous research, the results of analysis and discussion in this study, it can be concluded that: Organizational Culture, Organizational Citizenship Behavior and Work Discipline simultaneously have a significant influence and have a very significant effect on improving the performance of personnel. Organizational Culture, Organizational Citizenship Behavior and Discipline Work partially have a significant and significant influence in improving the performance of personnel. the Organizational Citizenship Behavior variable has a dominant influence in improving the performance of Pamekasan Police personnel. Keywords: Organizational Culture (X1), Organizational Citizenship Behavior (X2), Employee Discipline (X3) And Performance Personnel (Y)